Industrial forest plantations in Uganda: Local adjacent community perspectives - Byakagaba, Patrick; Muhiirwe, Ruth (Journal of Sustainable Forestry, 2017)
Industrial forest plantations are both hailed and vilified for their socio-economic effects on local communities. As such, we posed the following questions: (1) what opportunities do industrial forest plantations bring to local communities? and (2) what benefits are lost with the establishment of industrial forest plantations? Households neighboring industrial forest plantations in five villages of mid-western Uganda were surveyed. A large majority of the respondents (92.6%) stated that they had benefited from forest plantations, while a minority (7.4%) stated they did not. Fuelwood and employment were the most mentioned benefits. Approximately 47.9% of respondents stated that they had lost certain benefits due to the establishment of industrial forest plantations, while 52.1% stated they lost no benefits. Occupation, the number of people in a household and the length of residence in the area influenced responses on whether participants had lost certain benefits. Access to land was the most mentioned (82.2%) benefit lost due to industrial forest plantations. The study supports the notion that industrial forest plantations can provide certain benefits in the initial years of establishment but may also deny local communities historically established customary access and user land rights. Local livelihoods should be integrated into forest plantations management plans.
Keywords: Forest adjacent communities; Forest plantations; Land rights; Livelihoods